[tex]\bf -\cfrac{1}{3}x\div -\cfrac{1}{6}\implies -\cfrac{1}{~~\begin{matrix} 3 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}x\div -\cfrac{\stackrel{2}{~~\begin{matrix} 6 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{1}\implies 2 \\\\\\ \cfrac{5}{6}y\div -\cfrac{1}{6}\implies \cfrac{5}{~~\begin{matrix} 6 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}y\div -\cfrac{~~\begin{matrix} 6 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{1}\implies -5y \\\\[-0.35em] ~\dotfill[/tex]
[tex]\bf -\cfrac{1}{3}x+\cfrac{5}{6}y\qquad \implies \qquad -\cfrac{1}{6}\left( 2x-5y \right)[/tex]